(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The information revolution gave decision makers huge quantities of data available. Big data refers to datasets that are not just large, but also significant in diversity and speed and that make standard tools and approaches hard to handle. Because such data is fast growing, solutions should be explored and supplied so that these datasets are able to handle and extract value and information. In moreover, policymakers need to be able to get useful understanding into such diverse and fast changing data, from everyday transactions to contacts with customers and social network information. The Big Data Analytics, the deployment of advanced Big Data Analytics methodologies can deliver this value. The purpose of the article is to evaluate several analytical methods and means that may be used for Big Data and the potential that Big Data Analytics offers for the use of diverse decision-making areas.